Eco-Friendly Degumming Technology for Ramie Fiber. Issue 2 (3rd March 2016) - Biswas, Debkumar; Chakrabarti, Syamal Kanti; De, Samar; Paral, Rajkumar
Abstract : Ramie fiber represents almost 25–28% gum in its decorticated form. Unlike other common lignocellulosic bast fibers, e.g., jute, kenaf, etc., ramie is difficult to ret naturally. However, effective removal of gum from ramie determines its appropriate end-uses. In the present study, an eco-friendly degumming technology has been explained where pectinolytic and hemi cellulytic enzymes (pectinase, hemicellulase) in pure form have been mixed in a synergistic ratio to develop a unique ramie degumming formulation. Degumming of ramie with this new enzyme formulation has been investigated and the process is optimized considering loss in weight, tensile properties of degummed ramie fiber, and economy of processing. Residual gum content of 5.36% has been achieved at comparatively lower enzyme concentration (2.0% on wt. of fiber) under ambient temperatures (28–35°C) in a considerably less time (24 h). Tensile strength (17.85 g/tex) and corresponding fineness (0.74 tex) of degummed ramie fiber obtained under optimized degumming process substantiate its suitability in subsequent textile applications. Appearance and aesthetics of eco-degummed ramie fiber improved significantly (scanning electron microscopic pictures), which are beneficial for its commercial exploitation on industrial scale.